Performance Analysis Of Office Employees Of Technical Implementation Unit Of Transportation And Road Traffic Infrastructure In Region 1 Bantaeng Bantaeng Regency - Fikri Arzadilla; Edi Jusriadi; Hj. Naidah (International Journal of Economic Research and Financial Accounting, 2024)
This This research aims to determine the performance of employees at the UPT Sarana Prasarana Transportation and LLAJ Region 1 Bantaeng Office, Bantaeng district. Type of qualitative research. This research uses data obtained from interviews and documentation studies, with data analysis techniques using source triangulation. The results of the research show that the performance of employees at the UPT Sarana Prasaraa Perkomunikasi and LLAJ Region 1 Bantaeng offices is not very good. This is based on the results of interviews conducted with employees which stated that there are still many employees who do not meet performance assessment standards, are not disciplined in carrying out tasks on time and do not work according to the working hours set at the office. Apart from that, the work environment at the offices of UPT Sarana Perkomunikasi and LLAJ Region 1 Bantaeng is inadequate due to ineffective communication and inadequate office facilities.